2013
DOI: 10.5713/ajas.2013.13129
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Enzyme Complex on Performance, Intestinal Health and Nutrient Digestibility of Weaned Pigs

Abstract: Two experiments were conducted to evaluate the effect of supplementing a corn-soybean meal-based diet with an enzyme complex containing amylase, protease and xylanase on the performance, intestinal health, apparent ileal digestibility of amino acids and nutrient digestibility of weaned pigs. In Exp. 1, 108 piglets weaned at 28 d of age were fed one of three diets containing 0 (control), 100, or 150 ppm enzyme complex for 4 wks, based on a two-phase feeding program namely 1 to 7 d (phase 1) and 8 to 28 d (phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 41 publications
8
28
0
3
Order By: Relevance
“…In the results of in vitro tests, the addition of enzyme complexes (xylanase, protease and phytase) tended to increase the ileal digestibility of dry matter, even though it depended on test ingredients (Kong et al, 2015). Other studies also showed that enzyme mixtures including protease had a positive impact on nutrient digestibility, bacterial populations in the large intestine, and growth performance of weaned pigs (Yi et al, 2013), faecal nutrient digestibility of growing pigs (Ji et al, 2008), and the performance of growing pigs without improving apparent total tract digestibility (Jo et al, 2012). Recently, standalone proteases of swine diets have been used via several commercially available products (Guggenbuhl et al, 2012;Mc Alpine et al, 2012a, 2012bZuo et al, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…In the results of in vitro tests, the addition of enzyme complexes (xylanase, protease and phytase) tended to increase the ileal digestibility of dry matter, even though it depended on test ingredients (Kong et al, 2015). Other studies also showed that enzyme mixtures including protease had a positive impact on nutrient digestibility, bacterial populations in the large intestine, and growth performance of weaned pigs (Yi et al, 2013), faecal nutrient digestibility of growing pigs (Ji et al, 2008), and the performance of growing pigs without improving apparent total tract digestibility (Jo et al, 2012). Recently, standalone proteases of swine diets have been used via several commercially available products (Guggenbuhl et al, 2012;Mc Alpine et al, 2012a, 2012bZuo et al, 2015).…”
Section: Resultsmentioning
confidence: 98%
“…Xylanase supplementation has achieved inconsistent results [10,39]. In the present experiment, xylanase addition tended to improve CP digestibility and increased NDF digestibility.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, it may be beneficial to use a multienzyme preparation containing carbohydrases, protease, and phytase. Thus far, the use of exogenous enzymes to degrade NSP in corn-SBM-based diets has yielded inconsistent results, mainly because enzyme activities do not effectively hydrolyse the NSP present in corn and SBM (Willamil et al 2012;Yi et al 2013). However, Omogbenigun et al (2004) suggested that a combination of various enzyme activities is required to degrade complex NSP and improve nutrient utilization in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a combination of different enzyme activities is required for complete degradation of complex NSP and to improve nutrient utilization in pigs (Ji et al 2008;Jo et al 2012). Results of several experiments have indicated that dietary supplementation of multienzyme preparations can improve the growth performance and nutrient digestibility in pigs (Omogbenigun et al 2004;Yi et al 2013). Enzymes are beneficial to digest NSP in the diet if they can pass the stomach acidic environment.…”
Section: Introductionmentioning
confidence: 99%